2010
DOI: 10.5001/omj.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Level of Antiepileptic Drugs and their Side Effects

Abstract: There was no relationship between serum levels of AEDs and their side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Furthermore the patient experienced episodic toxic effects about 2 to 2.5 hours after drug intake; peak plasma concentration is reached in 2.5 to 12 hours after the oral intake of phenytoin and even earlier peaks have been reported (6). Previous research has reported these types of transient neurotoxic and ophthalmic side effects as occurred in this case during the first few hours of drug ingestion due to excessive fluctuation in plasma concentration of phenytoin between intake and time to peak plasma concentration (5).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Furthermore the patient experienced episodic toxic effects about 2 to 2.5 hours after drug intake; peak plasma concentration is reached in 2.5 to 12 hours after the oral intake of phenytoin and even earlier peaks have been reported (6). Previous research has reported these types of transient neurotoxic and ophthalmic side effects as occurred in this case during the first few hours of drug ingestion due to excessive fluctuation in plasma concentration of phenytoin between intake and time to peak plasma concentration (5).…”
Section: Discussionmentioning
confidence: 57%
“…The symptoms experienced by the patient in question are understandable in terms of the complex pharmacokinetics, narrow therapeutic index and individual variability in the metabolism and elimination of phenytoin. The patient developed exaggerated side effects gradually over a period of 6 weeks after the dosage increase, which can be explained by the gradual build up of the drug over the time as the pharmacokinetics of phenytoin follows a nonlinear path changing from first order kinetics to zero order; hence, even minor dosage changes can result in variable concentrations as the elimination is saturated (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a radical cure, epilepsy can only be treated symptomatically by preventing seizures (Beletsky & Mirsattari, ). Antiepileptic drugs (AEDs) are used to prevent epileptic seizures by selectively depressing the central nervous system and are effective only in 75–80% of patients, who often have to use AEDs throughout their lifetime (Hussein et al, ; Leppik, ; Ochoa, ). AEDs have important side effects, such as sedation, ataxia, gastrointestinal disorders, hepatoxicity, megaloblastic anemia, and cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…AEDs have important side effects, such as sedation, ataxia, gastrointestinal disorders, hepatoxicity, megaloblastic anemia, and cancer risk. Due to these side effects and limited efficacy, developing new AEDs is an important issue (Hussein et al, ). In addition, the use of AEDs in neurological and psychiatric indications such as migraine, neuropathic pain, bipolar disorder, and cancer in recent years has gained in importance (Dalkara & Karakurt, ; Fijałkowski, Sałat, Podkowa, Zarę, & Nowaczyk, ; Kudrow et al, ).…”
Section: Introductionmentioning
confidence: 99%